Association and Correlation between Temporomandibular Disorders and Psychological Factors in a Group of Dental Undergraduate Students - Sood, Divya; Subramaniam, Arun V; Subramaniam, Tulsi (International Journal of Applied Sciences and Biotechnology, 2014)
Aims/Objectives: To evaluate the prevalence and severity of temporomandibular disorders (TMD) and presence of psychological factors (i.e.,anxiety and depression levels) in dental undergraduate students. Second purpose was to assess the association and correlation between TMD degree and psychological factors viz. anxiety and depression. Materials and methods: The sample comprised of 400 Dental undergraduatestudents aged 18- 25 years, including both the genders. TMD degree was evaluated using an anamnestic questionnaire (modified version of Helkimo’s anamnestic index). Morphologic occlusion was evaluated according to Angle classification. The Hospital Anxiety and Depression Scale (HADS) was used to assess of levels of anxiety (HADSa) and depression (HADSd) in the dental undergraduate students. Results: Onbasisof the TMD anamnestic index, 74% of students were TMD free. 24.5% of subjects presented with mild degree of TMD and only 1.5% of subjects presented with moderate degree of TMD. According to the results obtained from HADSa, 35.3% of subjects presented with mild anxiety level, 13.8% with moderate anxiety level, and only 1.3% with severe anxiety level. According to the results obtained from HADSd, 10.3% of subjects presented with mild depression level and only 2.3% with moderate depression level. A definite association between TMD degree and Anxiety level (HADSa) was found. A definite association between TMD degree and Depression level (HADSd) was found. Therewas significant association between TMD degree and occlusion. Conclusions: On the basis of anamnestic index, this study revealed a 26% TMD prevalence in the dental undergraduate students included in the study; majority of cases being of mild degree. Both anxiety and depression were found to be associated with TMD degree/severity. Both anxiety and depression are weakly correlated with TMD in the present study. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11204 Int J Appl Sci Biotechnol, Vol. 2(4): 426-431